2016
DOI: 10.1002/chem.201602505
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Oxidative Addition of σ‐Bonds to Group 13 Compounds

Abstract: The oxidative addition reaction of X-H σ-bonds to Group 13 (E=Al, Ga, In) containing compounds has been computationally explored within the density functional theory framework. These reactions, which proceed concertedly involving the E(I) →E(III) oxidation, are exothermic and associated with relatively low activation barriers. In addition, the following trends in reactivity are found: (i) the activation barriers are lower for the X-H bonds involving the heavier element in the same group (ΔE(≠) : C>Si; N>P; O>S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 63 publications
3
19
1
Order By: Relevance
“…[15] There have been previous computational studies that have investigated the energetics of s-a nd p-bond activation by the NacNacAl I complex through direct oxidative addition. [17,[20][21][22][23] However, this work is the first to shed light on the explicit role of the aromatic solvent molecule, and show how it is able to considerably enhancethe potency of the NacNacAl I system.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…[15] There have been previous computational studies that have investigated the energetics of s-a nd p-bond activation by the NacNacAl I complex through direct oxidative addition. [17,[20][21][22][23] However, this work is the first to shed light on the explicit role of the aromatic solvent molecule, and show how it is able to considerably enhancethe potency of the NacNacAl I system.…”
Section: Introductionmentioning
confidence: 93%
“…More recently, the group of Nikonov also showed that the NacNacAl I complex could activate even stronger σ bonds, such as C−F, C−O, P−P, and C−S, and π bonds, such as C=S and P=S . It is believed that activation proceeds at a single group 13 metal center …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A structurally related TS has been calculated for the addition of H 2 to 1. 49,50 The geometry can be explained by considering the oxidative addition transition state in terms of a donation of electron density in the C]C p-bond to the vacant p-orbital on Al with concomitant back-donation from the Al sp 2 lone pair to the p* orbital of the alkene (vide infra).…”
Section: Dft Calculationsmentioning
confidence: 99%